2022
DOI: 10.3389/fpsyt.2022.881779
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Relationship Between Body Pain and Depressive Symptoms: A Pooled Analysis of Two National Aging Cohort Studies

Abstract: AimsTo investigate the bidirectional longitudinal association between pain and depressive symptoms and explore whether gender modifies the association.MethodsThis study used data of 17,577 participants without depressive symptoms and 15,775 without pain at baseline from waves 1–8 (2002/2003 to 2016/2017) of the English Longitudinal Study of Aging (ELSA) and waves 1 to 3 [2011–2015] of the China Health Retirement Longitudinal Study (CHARLS). Cox regression models were performed at the cohort level to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…9 Fibromyalgia and depression have been found to have a bidirectional temporal relationship, with 1 illness increasing the risk of developing another. 20,21 It is also known that individuals with persistent pain are more likely to meet diagnostic criteria for depression compared to those without pain 22 and the risk for developing depression is higher for individuals with multiple pain sites. 23 The impact of depression on the treatment of fibromyalgia has been unclear.…”
Section: Introductionmentioning
confidence: 99%
“…9 Fibromyalgia and depression have been found to have a bidirectional temporal relationship, with 1 illness increasing the risk of developing another. 20,21 It is also known that individuals with persistent pain are more likely to meet diagnostic criteria for depression compared to those without pain 22 and the risk for developing depression is higher for individuals with multiple pain sites. 23 The impact of depression on the treatment of fibromyalgia has been unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A pooled analysis of two national aging cohort studies showed that a bidirectional association exists between pain and depressive symptoms. People with pain were at a higher risk of suffering from depressive disorders and vice versa [ 49 ]. Our study showed that postoperative pain was an independent risk factor for depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies show a bidirectional association between physical activity and knee pain [24]. On the other hand, some other studies found a bidirectional association between pain and sleep problems [25] and poor mental health (depressive symptoms) [26].…”
Section: Discussionmentioning
confidence: 99%